Examining service‐user perspectives for the development of a good outcome checklist for individuals at clinical high risk for psychosis. Issue 3 (26th May 2020) - Petros, Natalia; Cullen, Alexis E.; Vieira, Sandra; Rowland, Emma; King, Georgina; Leung, Wing See; Fusar‐Poli, Paolo; Mechelli, Andrea; McGuire, Philip
Abstract: Aims: Around 15% of patients at clinical high risk for psychosis (CHR‐P) experience symptomatic remission and functional recovery at follow‐up, yet the definition of a good outcome (GO) in this population requires further development. Outcomes are typically designed and rated by clinicians rather than patients, to measure adverse as opposed to GOs. Here we investigate how CHR‐P subjects define a GO, with the aim of developing a checklist that could be used to measure GO in this clinical group. Methods: A set of GO‐focused questions were designed in collaboration with a service‐user. CHR‐P patients (n = 48) were asked to rate the importance of items that could indicate short‐term (1 year) and long‐term (5 years) GO. These items were then ranked using the relative importance index (RII). Results: Patients rated improvement in subjective wellbeing (RII = 0.829) and non‐specific presenting symptoms (RII = 0.817) amongst the factors most important for indicating GO in the short‐term, and improved resilience (RII = 0.879) and negative symptoms (RII = 0.858) as key items for indicating long‐term GO. Patients regarded building resilience (RII = 0.842) and having support from mental health services (RII = 0.833) as being protective for their mental health. These measures were included in a preliminary 12‐item GO checklist (GO‐12) for assessing GO in CHR‐P subjects. Conclusions: Patient‐defined measures of GO included items that are not incorporated into conventional measures of outcomes in CHR‐P subjects, such as subjective wellbeing and resilience. Integrating patient‐defined metrics of GO may improve the assessment of outcomes in the CHR‐P population.